Control de ingresos y gastos de la empresa comercial tiñe en el 2020 - Gavica Bajaña, Arelis Andrea (2021)
The commercial company Tiñe has been operating since 2017, starting as a small family business, but due to the popularity it has been obtaining, it grew until it became a Commercial company, which are the type of companies that are solely dedicated to the purchase and sale of goods that can be raw materials or final products. Most of its products are basic necessities, so it is a company that has a lot of activity on a daily basis. For this company to be maintained, it must not only depend on the purchase or sale of its products, but it is also necessary that the administration begins to make financial decisions that bring benefits, such as expanding the company, which has been done compared to its beginnings, in addition to knowing how to correctly keep the commercial data and with the indicated calculations, present a more precise financial statement, allows the company to know more precisely how it is in a certain period of time. During 2020, the company Tiñe has been presenting problems with the control of income and expenses records, so that they do not know the values and if the company during that period was doing things financially well. The following work is in charge of reviewing the data available to the company during this period and making the respective calculations to know if the company is in a good financial situation, following the respective sub-line of research established by the Technical University of Babahoyo.